Oral health status of cracker workers in Sivakasi, Tamil Nadu, India - A cross-sectional study - M Mary Sherley; A Nivetha; R Ganesh (Wolters Kluwer Medknow Publications, 2015)
Introduction: Poor oral health and untreated oral diseases have a significant impact on quality of life. Oral and general health of cracker workers is in association with their working environment. Aim: To assess the oral health status of cracker workers in Sivakasi. Materials and Methods: A total of 350 subjects were included in this study. The subjects were randomly selected from 10 companies in Sivakasi. Data were collected by using WHO Oral Health Assessment Form for Adults (2013). The proforma included questions on knowledge, attitude, and practices of oral hygiene. Statistical analysis was performed using statistical package for social sciences version 16.0. Results: Among 350 subjects, 34.9% were males and 65.1% were females. The mean number of decayed, missing, and filled teeth was 2.52, 4.17, and 1.32, respectively. The mean of sextants with shallow pockets is 5.9 and its percentage is 54. The mean of sextants with deep pockets is 1.5 and its percentage is 14.6. Oral lesions were found to be present among 4.3% of study subjects. Conclusion: Workers of fireworks industries those with dental caries, periodontal problems, and other dental complaints should be examined repeatedly for their oral health status.